Profitability and Value Chain Analysis of Cashew Nuts in Bandarban Hill District of Bangladesh (Journal of the Bangladesh Agricultural University, 2025)
Cashew nut cultivation is emerging as a promising agricultural activity in the Bandarban hill district of Bangladesh, offering significant economic potential in domestic and international markets for small-scale farmers and agribusiness enterprises. The present study analyses the profitability, value chain and the existing challenges of cashew nut production. In the Bandarban hill district, 90 cashew nut growers and 23 market intermediaries were purposively selected from the Rowangchari, Ruma, and Thanchi upazilas through face-to-face interviews. Descriptive analysis including Net Return, Gross Margin, Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR) and Value Chain Analysis were used to analyze the data. On average, per hectare yield of cashew nuts was zero in the first year and 1,610 kg per hectare in 5-25 years. The total costs were Tk. 68,781 per hectare per year and Tk. 128 per tree per year. Though the gross return was zero in the first four years, the estimated gross and net returns per hectare per year for the next five to twenty-five years were Tk. 1,77,100 and Tk. 1,08,319 respectively. The NPV, BCR, and IRR were found as Tk. 7,75,050, 1.76 and 34%, respectively, in the study area. In the cashew nut value chain, the Faria (who collects the nuts from the farmers and transports them to the market) added the lowest value of Tk. 3 per kg (2.73%), whereas the processor added the highest value of Tk. 37 per kg (26.81%) in the cashew nut value chain. The study identified that irrigation was the major problem, followed by labor scarcity, and high transportation costs. The findings of this study might be helpful for policy-making as well as the development of cashew nut production and marketing systems in Bangladesh.J Bangladesh Agril Univ 23(1): 59–70, 2025